(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the study of the history of education, identity and dynamics of changes in the national composition of the population of the city of Kyzylkiya during the years of independence, based on local materials. As a result of the political and economic crisis and the closure of industrial enterprises in the city, unemployment has increased, and workers from the city’s enterprises have emigrated to Kazakhstan and Russia. As a result of external and internal emigration, the national composition of the city’s population has changed. The article is based on the results of scientific research on changes in the national composition of the city’s population.